Identification of the Active Compound of Ethyl Acetate Fraction of Yellow Root Extract (Fatoua pilosa Gaudich) - Maria Magdalena Nona Motu Tukan (Indonesian Journal of Chemistry and Environment, 2026)
Yellow root (Fatoua pilosa Gaudich) is a weed plant that comes from the morceae family. This plant can grow up to 60 cm tall and can survive in dry soil conditions. Empirically, the yellow root plant is used by the people of East Flores Regency as an anti-diabetic drug. When using it, 2 grams of yellow root is boiled in 400 mL of water, then filtered and the water is drunk. This study aims to identify the active compounds found in yellow roots (Fatoua pilosa Gaudich) from East Flores Regency. The research was conducted in December 2024 at the Fisheries Product Technology Laboratory, Larantuka Teacher Training and Technology Institute and continued at the Central Jakarta Basic Health Laboratory. The main material used in this study was yellow root (Faoua pilosa Gaudich) which was taken from East Flores Regency. Sample extraction was carried out using the maceration method with a ratio of 1:10 between yellow root and 70% ethanol. The ethanol extract was then fractionated with ethyl acetate solvent, then the compounds were identified using LC-MS/MS. The research results show that the ethyl acetate extract of yellow root contains 8 active compounds with varying activities. These 8 compounds include 2,4-Pentadiynylbenzene, Propionaldehyde, beta-Lysylmethanediamine, Phellodenol-A, N-(1-adamantyl)-3-[16-[3-(1-adamantylamino)-3-oxopropanoyl]-1,4,10,13-tetraoxa-7,16-diazacyclooctadec-7-yl]-3 oxopropanamide, Ethyl 2-acetylheptanoate, Lupeol, Deferoxamine.